2018
DOI: 10.1002/pchj.228
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the psychodrama in instilling empathy and self‐awareness: A pilot study

Abstract: This pilot study investigated the effects of psychodrama on the counseling skills (mainly empathy) and on increasing the self-awareness of 23 counseling undergraduate students. Participants attended 12 psychodrama sessions over 3 months. Data were gathered by using the Empathic Tendency Scale and a personal information form. The study used the mixed method research design, which combines qualitative and quantitative methods. The quantitative aspect of the study involved the use of pretest-posttest experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
1
12
0
2
Order By: Relevance
“…It was found that psychodrama increased empathy, counselling skills and self-awareness in students (49) .…”
Section: Resultsmentioning
confidence: 95%
“…It was found that psychodrama increased empathy, counselling skills and self-awareness in students (49) .…”
Section: Resultsmentioning
confidence: 95%
“…Finally, four clinical trials were carried out with community samples. The aim was to help participants develop professional competencies [ 72 , 74 ] or personal strengths that would have a positive impact on their mental health [ 64 , 75 ]. Thus, Özbas and Tel [ 72 ] implemented a program of psychodrama treatment designed to improve the quality of professional care provided by oncology nurses.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of the program was to increase perceived levels of psychological and work-related empowerment and decrease burnout levels among nursing staff. The results reported by Dogan [ 74 ] were positive, with psychodrama being found to instill professional competencies such as empathy and self-awareness in students enrolled in a psychological counseling and guidance course. In a previous study, this same author [ 64 ] analyzed the consequences of an intervention on romantic attachment among adults.…”
Section: Resultsmentioning
confidence: 99%
“…Psychological resilience is defined as the ability to face, accept, adapt, and take measures against challenges and threats or stressful events. 29,30 Psychological resilience can be referred to as the perception of positive changes, such as personal growth, resulting from the experience of advanced cancer. We believe that if resilience increases, coping strategies will be developed.…”
Section: Discussionmentioning
confidence: 99%